h+(-3)+9=-1+14

Simple and best practice solution for h+(-3)+9=-1+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h+(-3)+9=-1+14 equation:


Simplifying
h + (-3) + 9 = -1 + 14
h + -3 + 9 = -1 + 14

Reorder the terms:
-3 + 9 + h = -1 + 14

Combine like terms: -3 + 9 = 6
6 + h = -1 + 14

Combine like terms: -1 + 14 = 13
6 + h = 13

Solving
6 + h = 13

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + h = 13 + -6

Combine like terms: 6 + -6 = 0
0 + h = 13 + -6
h = 13 + -6

Combine like terms: 13 + -6 = 7
h = 7

Simplifying
h = 7

See similar equations:

| -6x^2+5x-2=0 | | 10a=3a+9+6a | | Y-16=11(x-1) | | b^4-5b^2-6b=0 | | .77=(1/x) | | x^4+9x^2+4=0 | | .77=1/x | | x/24-1.4=8.3 | | (X+4)-x-(5-6x)=11 | | Y=(6x+3)10 | | 8x+6y=-26 | | 2a+4(2-a)-6(1+a)=18 | | m+(-6)=22 | | 15+4ln(x)=10 | | Z-19=19 | | 2(x+6)=-2x(x-4) | | 5.25=1.25 | | 5[x+9]=80 | | Y=5.5x+15 | | X+0.5y=7 | | 3C+7+5c=4c+31 | | 8x+-2=60 | | 6x+2=8x-26 | | (3x+4)(x^2+14x+40)=0 | | 5/2u=20 | | 5i/8-3i | | 2(i+2)-9=-17-i | | 7x/2=(5x-4)/3 | | ln(x)+ln(x+-6)=ln(8x-24) | | 15x^2+x=75 | | -105=-7(2k+1) | | (x+3)+2=0 |

Equations solver categories